Note on a Silver Reliquary bequeathed by E W A D Hay, found among his coins (Proceedings of the Society of Antiquaries of Scotland, 1856)
A reliquary was found amongst the donated coin collection of E W A D Hay. The author believes that Mr Hay may not have known that it was included in his donation. Meeting notes for 14 February, 1855 are appended.